LandSIM3D: modellazione in real time 3D di dati geografici - Lambo Srl, Lambo Srl (GEOmedia, 2009)
LandSIM3D: realtime 3D modelling of geographic data LandSIM3D allows to model in 3D an existing landscape in a few hours only and geo-referenced offering great landscape analysis and understanding tools. 3D projects can then be inserted into the existing landscape with ease and precision. The project alternatives and impact can then be visualized and studied into their immediate environmental. The complex evolution of the landscape in the future can also be simulated and the landscape model can be manipulated interactively and better shared with colleagues. For that reason, LandSIM3D is different from traditional 3D imagery solutions, normally reserved for computer graphics experts. For more information about LandSIM3D, go to www.landsim3d.com.